2012
DOI: 10.1155/2012/687909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcranial Brain Stimulation for the Treatment of Alzheimer Disease: A Review

Abstract: Available pharmacological treatments for Alzheimer disease (AD) have limited effectiveness, are expensive, and sometimes induce side effects. Therefore, alternative or complementary adjuvant therapeutic strategies have gained increasing attention. The development of novel noninvasive methods of brain stimulation has increased the interest in neuromodulatory techniques as potential therapeutic tool for cognitive rehabilitation in AD. In particular, repetitive transcranial magnetic stimulation (rTMS) and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 44 publications
1
52
0
1
Order By: Relevance
“…This should be taken in account when talking about inhibitory or excitatory effects. Hippocampus is an important area in the formation of recognition memory in both human and animals (Norman and Eacott, 2004) and perirhinal cortex has also been suggested that could play an important function in object recognition (Nardone et al, 2012). In addition, the favorable effects of no invasive stimulation may be enhanced if we stimulate a cortical area which is implicated in the execution of a training task.…”
Section: Discussionmentioning
confidence: 99%
“…This should be taken in account when talking about inhibitory or excitatory effects. Hippocampus is an important area in the formation of recognition memory in both human and animals (Norman and Eacott, 2004) and perirhinal cortex has also been suggested that could play an important function in object recognition (Nardone et al, 2012). In addition, the favorable effects of no invasive stimulation may be enhanced if we stimulate a cortical area which is implicated in the execution of a training task.…”
Section: Discussionmentioning
confidence: 99%
“…epetitive transcranial magnetic stimulation (rTMS) is a noninvasive neuromodulation technique that has been closely examined as a possible treatment for neurodegenerative diseases (Chou et al, 2015;Nardone et al, 2012). It delivers repeated magnetic pulses through a stimulation coil placed over the scalp to generate a relatively focal electromagnetic field capable of triggering action potentials in neurons (Barker et al, 1985;Rothwell, 1991).…”
mentioning
confidence: 99%
“…It delivers repeated magnetic pulses through a stimulation coil placed over the scalp to generate a relatively focal electromagnetic field capable of triggering action potentials in neurons (Barker et al, 1985;Rothwell, 1991). Although accumulating evidence suggests that rTMS can be utilized to enhance motor or cognitive function in patients with neurodegenerative diseases (Chou et al, 2015;Nardone et al, 2012), little is known about how the rTMS modulates deeper brain regions that are functionally connected to the stimulation site and how these changes correlate with improvement of symptoms.…”
mentioning
confidence: 99%
“…These findings are very preliminary, since improving performances in a single task does not necessarily represent a global cognitive enhancement. 6 With respect to these chronic neurologic disorders, the application of rTMS and tDCS in monophasic diseases such as ischemic stroke holds great promise. The ability of transcranial stimulation to enhance (or reduce) the cortical activity of the lesioned (or the unaffected) hemisphere has been used to ameliorate motor impairment, poststroke depression, and cortical deficits in chronic stroke patients.…”
mentioning
confidence: 99%